Successful Laparoscopically Assisted Transcervical Suction Evacuation of Interstitial Pregnancy following Failed Methotrexate Injection in a Community Hospital Setting - Rani B. Fritz; Neal Rosenblum; Kecia Gaither; Alonzo Sherman; Alwyn McCalla (Case Reports in Obstetrics and Gynecology)
We report on a case of a patient with an early diagnosed cornual ectopic pregnancy following failed methotrexate treatment. The patient was subsequently taken to the operating room for a laparoscopic guided transcervical suction curettage of the cornual ectopic. The surgery was successful and the patient was followed up until her urine pregnancy test was negative. We conclude that in properly selected patients, cornual ectopic pregnancy may be treated with transcervical suction curettage.